Effectiveness of Online Cognitive Behavioral Intervention on Procrastination and Academic Stress - Turan, Selva; Rahman, Farhana. (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This study aimed to evaluate the effectiveness of an online cognitive-behavioral therapy (CBT) intervention in reducing procrastination and academic stress among university students. Methods and Materials: A randomized controlled trial (RCT) was conducted with 30 university students from Bangladesh, who were randomly assigned to either the intervention (online CBT) group (n = 15) or the control group (n = 15). The intervention consisted of eleven weekly online CBT sessions, each lasting 45 to 60 minutes. Procrastination and academic stress were measured using the Procrastination Assessment Scale for Students (PASS) and the Academic Stress Scale (ASS) at three stages: pre-intervention, post-intervention, and four-month follow-up. Data were analyzed using repeated measures analysis of variance (ANOVA), with Bonferroni post-hoc tests to assess changes within and between groups. Findings: The results indicated that the intervention group showed significant reductions in both procrastination (F = 7.85, p = 0.002) and academic stress (F = 6.32, p = 0.006) across the three stages. The intervention group’s procrastination scores decreased from pre-intervention (M = 63.27) to post-intervention (M = 48.51) and were maintained at follow-up (M = 47.12). Similarly, academic stress scores dropped from pre-intervention (M = 55.36) to post-intervention (M = 42.14) and remained lower at follow-up (M = 41.05). The control group showed no significant changes. Bonferroni post-hoc tests confirmed these findings, with significant mean differences in procrastination and stress at various stages. Conclusion: The online CBT intervention was effective in significantly reducing procrastination and academic stress among university students, with these improvements maintained over a four-month follow-up period. This supports the utility of online CBT as a feasible and effective tool for addressing procrastination and stress in academic settings.